Micropatterning kinetics of different glass-forming systems investigated by thermoplastic net-shaping. (August 2017) - Sarac, Baran; Bera, Supriya; Spieckermann, Florian; Balakin, Sascha; Stoica, Mihai; Calin, Mariana; Eckert, Jürgen
Abstract: The formability difference between good and marginal glass-forming systems is investigated by micro-surface patterning of hierarchical features using thermoplastic net-shaping (TPN). For each alloy, a remarkable change in the flow behaviour is observed as the applied force along with the pressing time and temperature are optimized. The flow kinetics of glassy alloys with different glass-forming abilities is best described by the formability parameter S, which is defined by the ratio of the width of the supercooled to undercooled liquid region ( T l − T g )/( T x − T g ). Reproducible micro-engineered surfaces with high uniformity can be established by controlled TPN processing. Graphical abstract: